Strategi Pengembangan Wisata Budaya di Kawasan Pecinaan Lasem - Ariyaningsih Ariyaningsih (SPECTA Journal of Technology, 2018)
Lasem is one of the sub-districts in Rembang District with historical and cultural heritage of Chinesse that have the potential for the development of cultural tourism as well as introducing to the wider community. The potential is still not utilized and developed optimally. This study was conducted to formulate strategies of cultural tourism development in accordance with the potential problems in the region.The analysis used is AHP(Analysis Hierarcy Process) combination SWOT analysis to determine strategy of development of Lasem Chinatown Area. In achieving the objectives of this study identified the strengths, weaknesses, opportunities, and threats that exist in the Lasem Pecinan Region. Then, the results of observationwere processed in the form of AHP analysis and generated the factor with the most important weight is the financing of development and attractiveness of the building. The next step, comparing the selected SWOT factor to produce the strategy component. The strategy was reprocessed using AHP to get priority of Lasem's area development strategy.The study found that the strategy of making tourism route, financing strategy for tourist attraction, the improvement of tourism accessibility, the development of tourism based on community empowerment, and the provision of supporting facilities in the tourism area. In addition, the first priority of strategy is the improvement of accessibility.